1976
DOI: 10.1016/0042-6989(76)90077-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normal and dichoptic colour mixing

Abstract: Abstract-Dichoptic mixtures of equiluminous components of different wavelengths were matched with a binocularly presented "monocular" mixture of appropriate chosen amounts of the same colour components. Stimuli were chosen from the region of 490-630 nm. Although satisfactory colour matches could be obtained, dichoptic mixtures differed from normal mixtures to a considerable extent. Midspectral stimuli tended to be more dominant in the dichoptic mixtures than either short or long wavelength stimuli. An attempt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The direction of these shifts was reminiscent of the confusion lines of the chromatic defective observers, or they followed directions that converged at the position of the green primary of 530 nm, the component that prevails in dichoptic mixtures. 33 This preponderance is probably one of the reasons why dichoptic mixtures seem brighter than monoptic ones, 32,33,37 a fact we have observed once again in the experiments presented in this article.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The direction of these shifts was reminiscent of the confusion lines of the chromatic defective observers, or they followed directions that converged at the position of the green primary of 530 nm, the component that prevails in dichoptic mixtures. 33 This preponderance is probably one of the reasons why dichoptic mixtures seem brighter than monoptic ones, 32,33,37 a fact we have observed once again in the experiments presented in this article.…”
Section: Introductionmentioning
confidence: 57%
“…33 A review by Hovis 34 and, more recently, another in Howard and Rogers 35 deserve to be consulted.…”
Section: Introductionmentioning
confidence: 97%
“…Less rivalry with increasing spatial contrast 19,23,36 Observation duration More rivalry with increasing duration from 1 to 1000 ms 37 More rivalry up to 250 ms, after which becomes constant 18 Less rivalry with increasing duration from 2 to 6 s 22 Less rivalry with 3 s than 500 ms 38 Disparity Less rivalry with decreasing disparity relative to no disparity for crossed disparity while more rivalry with increasing disparity for uncrossed disparity 39 rivalry perception. It would be of interest to test each observer's color discrimination ability with the Farnsworth-Munsell 100-Hue Test and see if it correlates with the inter-observer variations in binocular rivalry thresholds.…”
Section: Factors Effectsmentioning
confidence: 99%
“…In the case where the green light was presented to the dominant eye, a smaller amount of green light was needed to match the reference color. Conversely, when the green light was presented to the nondominant eye, opposite results were obtained, indicating that the binocular mixture required a greater amount of green light to achieve a color match [10,11]. Furthermore, Lin et al observed that the contrast of the binocular mixture was slightly biased by the patch contrast of the dominant eye [12].…”
Section: Introductionmentioning
confidence: 99%